The Analysis of Construction Management According to the Philosophy of Utilitarianism by John Stuart Mill - Chongstitrak, Kasem; Thongpan, Suwin; Leeka, Jaras (Journal of Graduate MCU KhonKaen Campus, 2025)
The research entitled “The Analysis of Construction Management According to the Utilitarian Philosophy of John Stuart Mill” aimed to: 1) study construction management, 2) examine John Stuart Mill’s utilitarian philosophy, and 3) analyze construction management in accordance with John Stuart Mill’s utilitarian perspective. This study employed documentary research methodology by investigating primary sources, including the original works of John Stuart Mill, and secondary sources, including books, academic articles, and related research studies. Data were analyzed through descriptive and inductive analytical methods. The findings revealed that: 1) construction management based on the 4M concept, consisting of Man, Money, Machine, and Material, serves as an essential framework for enhancing project efficiency and achieving successful outcomes in terms of time, cost, and quality control 2) John Stuart Mill’s utilitarian philosophy emphasizes actions that generate the greatest happiness and benefit for the greatest number of people while respecting individual rights, freedom, and social responsibility 3) the application of utilitarian philosophy to construction management suggests that effective management of human resources, financial resources, machinery, and construction materials should be conducted alongside considerations of public benefit, social responsibility, and environmental sustainability. Such an approach contributes to project success, cost-effectiveness, waste reduction, and the maximization of benefits for all stakeholders. Furthermore, it promotes sustainable development and aligns with Mill’s Greatest Happiness Principle, which advocates creating the highest level of well-being for society as a whole.